A novel miR1983-TLR7-IFNβ circuit licenses NK cells to kill glioma cells, and is under the control of galectin-1. (1st January 2021) - Shah, Diana; Comba, Andrea; Faisal, Syed M.; Kadiyala, Padma; Baker, Gregory J.; Alghamri, Mahmoud S.; Doherty, Robert; Zamler, Daniel; Nuñez, Gabriel; Castro, Maria G.; Lowenstein, Pedro R.
ABSTRACT: Although pharmacological stimulation of TLRs has anti-tumor effects, it has not been determined whether endogenous stimulation of TLRs can lead to tumor rejection. Herein, we demonstrate the existence of an innate anti-glioma NK-mediated circuit initiated by glioma-released miR-1983 within exosomes, and which is under the regulation of galectin-1 (Gal-1). We demonstrate that miR-1983 is an endogenous TLR7 ligand that activates TLR7 in pDCs and cDCs through a 5ʹ-UGUUU-3ʹ motif at its 3ʹ end. TLR7 activation and downstream signaling through MyD88-IRF5/IRF7 stimulates secretion of IFN-β. IFN-β then stimulates NK cells resulting in the eradication of gliomas. We propose that successful immunotherapy for glioma could exploit this endogenous innate immune circuit to activate TLR7 signaling and stimulate powerful anti-glioma NK activity, at least 10–14 days before the activation of anti-tumor adaptive immunity.